Garbage Monitoring System Ready to Transport with Sensor LiDAR Based on Wireless Sensor Network - Akuwan Saleh; Rafi Ganendra W; Prima Kristalina (IJAIT (International Journal of Applied Information Technology), 2022)
The transition of the waste management flow scheme from conventional to modern will be implemented in Indonesia as a whole, considering the national target of reducing waste to 70% by 2025 (Indonesia Presidential Regulation No. 97 of 2017). The high level of waste productivity makes the modern method of transporting garbage by truck (compactor) to each garbage node more efficient. This method has begun to be applied in various cities in Indonesia. However, this method is still dependent on service time, the number of trucks, and limited human resources (HR), which are the causes of the lack of efficiency in waste management in Indonesia. The result of this research is that the intensity of the waste from each node of the trash bin at the TPS can be monitored on the web. The reading data from the LiDAR sensor will be processed using the Time-of-flight method and then sent into ready-to-transport waste intensity data, which will be updated every second (real-time) by each waste node. The waste intensity is classified as complete if the sensor reading is 0-20 cm. marked red on the website, moderate waste intensity if the sensor reads 21-60 cm, marked orange on the website, and empty if the sensor reads 61-120 cm marked white on the website. The results obtained from monitoring the intensity of this waste can help parties and agencies that need information on the intensity of waste at each waste node to maximize waste management.